Towards the Text Compression Based Feature Extraction in High Impedance Fault Detection - Vantuch, Tomáš; Prílepok, Michal; Fulneček, Jan; Hrbáč, Roman; Mišák, Stanislav (Energies (Basel), 2019)
High impedance faults of medium voltage overhead lines with covered conductors can be identified by the presence of partial discharges. Despite it is a subject of research for more than 60 years, online partial discharges detection is always a challenge, especially in environment with heavy background noise. In this paper, a new approach for partial discharge pattern recognition is presented. All results were obtained on data, acquired from real 22 kV medium voltage overhead power line with covered conductors. The proposed method is based on a text compression algorithm and it serves as a signal similarity estimation, applied for the first time on partial discharge pattern. Its relevancy is examined by three different variations of classification model. The improvement gained on an already deployed model proves its quality.